2014
DOI: 10.1007/s12132-014-9236-2
|View full text |Cite
|
Sign up to set email alerts
|

Slum Tourism and Urban Regeneration: Touring Inner Johannesburg

Abstract: Much attention has been paid to township tourism in South Africa, a practice of tourism that emerged in Apartheid South Africa with different organised tours catering for governmental officials, faith-based groups and anti-apartheid activists. In democratic South Africa township tourism has developed into a mainstream tourism activity and operators now offer township tours, township stays and other tourist activities in townships across rural and urban South Africa. Township tourism has also been one central e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Moreover, the question could be raised to what extent slum tourism was the pioneering tourism activity in downtown Johannesburg. With its success that I described in my research (Frenzel 2014(Frenzel , 2016 what role did slum tourism have in prompting a wider urban tourism phenomenon that no longer makes poverty into a theme? This is particularly relevant, as evidence from other African cities seems to suggest that slum tourism is often the first form of urban tourism to emerge.…”
Section: Conclusion and Further Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the question could be raised to what extent slum tourism was the pioneering tourism activity in downtown Johannesburg. With its success that I described in my research (Frenzel 2014(Frenzel , 2016 what role did slum tourism have in prompting a wider urban tourism phenomenon that no longer makes poverty into a theme? This is particularly relevant, as evidence from other African cities seems to suggest that slum tourism is often the first form of urban tourism to emerge.…”
Section: Conclusion and Further Researchmentioning
confidence: 99%
“…Walking Tours in the Johannesburg Inner City^, Hoogendoorn and Giddy (2017) present findings from their research on inner city tourism in South Africa's largest city that I observed and first discussed in Urban Forum in 2014 in a paper titled: BSlum Tourism and Urban Regeneration: Touring Inner Johannesburg^ (Frenzel 2014).…”
Section: Introductionmentioning
confidence: 98%
“…After all, as Hallin and Dobers (2012) state, 'the guided tour, regardless of its intention, is political in nature'(23). Frenzel (2014) even goes so far as to argue that slum tourism forms part of wider urban regeneration from below, given that it 'responds to an absence of action or perceived failure to respond to poverty by urban policy' (431). Tourism, thus, has the power to acknowledge communities marginalised by the government and put them back on the map (Frenzel 2014).…”
Section: Homeless Tour Guiding In the Context Of Slum And Poverty Toumentioning
confidence: 99%
“…They are using such tourism as the means of welfare of such societies (Booyens 2010;Koens 2012;Ramchander 2007;Rogerson 2004, 2013, Frenzel 2014. The majority of their profit goes to school education, cleanliness of streets, health related issues.…”
Section: Debate Surrounding Reality Tourism (Challenges and Criticism)mentioning
confidence: 99%